Genesis and Structure of Highest Moral Value in Kantian Philosophy - Burovas, Valerijus (Problemos, 1979)
The analysis of the highest moral value is done in the context of transition of theoretical reason to practical one taking into account the evolution of the ideas of critical transcendentalism. The structure of the Highest Good is revealed through an immanent and actual transition from theory to practice. The former is achieved by an inner “reappraisal of values”, the latter – through solving the antinomy of freedom and necessity.